A locally advanced squamous cell carcinoma of buccal mucosa with extreme skin involvement managed surgically: a case report - Chhabra, Dishant; Thakral, Riya; Arora, Amit (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Squamous cell carcinoma (SCC) of the buccal mucosa represents a prevalent subtype of oral malignancy, particularly among individuals with habitual tobacco and betel nut use. In advanced stages, the disease may exhibit rapid progression with invasion into adjacent anatomical structures, complicating therapeutic management. We report a case involving a 66-year-old female, Mrs. XY who presented with a large, ulceroproliferative lesion on the left hemiface. The lesion originated as a minor mucosal lesion and was initially managed with alternative medicine, ultimately progressing to involve cutaneous, muscular, and bony structures. Cross-sectional imaging revealed extensive local invasion, and histopathological analysis confirmed a moderately differentiated keratinizing SCC. The patient underwent bite composite resection, right radical neck dissection left modified radical neck dissection, and immediate reconstruction with a pectoralis major myocutaneous (PMMC) flap along with anterolateral thigh flap. The pathological staging was pT4aN3b with evidence of perineural and lymphovascular invasion and extranodal extension. This case underscores the aggressive nature of untreated oral SCC and highlights the necessity of early diagnosis, timely oncologic intervention, and multidisciplinary management in improving patient outcomes.